COMPARISON OF CENTERING ABILITY AND TRANSPORTATION OF THE PROTAPER NEXT AND ONESHAPE FILE ROTARY SYSTEMS FOR PREPARING SIMULATED CURVED CANAL - Kamil Zafar; Sheikh Bilal Badar; Robia Ghafoor; Farhan Raza Khan (Journal of Ayub Medical College Abbottabad, 2021)
Background: To compare the effect of ProTaper Next and One Shape rotary files on canal transportation and centering abilities in resin block with simulated curved canal. Methods: An in-vitro experimental study was carried out in Dental clinics. Sixty resin blocks (30 per group) having simulated curved canals prepared with ProTaper Next and One Shape and then filled with red and blue Indian ink, respectively. Photographs of resin blocks obtained using standardized manner were then transferred to the adobe photoshop 7.0. Centering abilities and amount of transportation were then calculated at coronal, middle and apical portion of canal for both the groups. Independent sample t-test was used to compare the transportation and centering ability of both file systems. Level of significance was kept at p-value ‰¤0.01. Results: One Shape file resulted in more canal transportation at all the levels (apical, middle and coronal part) as compared to ProTaper Next file, however, difference was not statistically significant (p-value >0.01). Statistically significant difference was noted at the apical third between these two rotary files with One Shape file showing more centered preparation as opposed to ProTaper Next file (p-value <0.01). Conclusion: One Shape file system had more centered canal preparations specifically at the apical region as compared to ProTaper Next. One Shape also lead to more canal transportation in comparison to ProTaper Next, however the difference was not statistically significant.